Semantic Study Of The Arabic Text The Quran Verses: Educational Implications Regarding Individual Responsibility And Its Application - Alsubaie, Faisal Bin Shabib Mosleet (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aimed to derive educational contents from the verses on individual responsibility mentioned in the Qur’an, and from this primary goal emerge the following sub-goals: deducing educational principles from the verses on individual responsibility, explaining the educational values deduced from the verses on individual responsibility and highlighting contemporary educational applications deduced from the verses on individual responsibility, which reached ten verses. The study relied on the descriptive approach—the deductive analytical method in extracting educational contents from the specific verses. The study results indicated that the Holy Qur’an, including its verses on individual responsibility, includes many educational contents of principles and values, which we must work to derive to be applied in the educational field. The study clarified the principles of individual responsibility that should be developed in young people, the most important of which are justice, self-control, bearing responsibility, self-struggle, and decision-making. The study also resulted in values derived from the verses of individual responsibility, the most important of which are fear of Allāh, warning against injustice to the soul, spending, purifying the soul, gratitude, good deeds, and modesty. The study highlighted the educational importance of each principle and value mentioned in the noble verses and that each value significantly impacts human life. The study also presented some contemporary educational applications that can be exploited and applied in developing individual responsibility through the family and school.